Back Cover: Electrochemical Sensor Based on AgNPs‐NNH Nanocomposites for Hydrogen Peroxide Detection by Zero Current Potentiometry (Chin. J. Chem. 12/2018). Issue 12 (13th November 2018) - Fu, Yanyi; Hao, Huan; Liu, Xiaoli; Zheng, Jianbin
Abstract : The back cover picture shows a zero current potential technique for electrochemical sensing of hydrogen peroxide based on silver‐nickel nitrate hydroxide (AgNPs‐NNH). By using the AgNPs‐NNH nanocomposites, a very low detection limit of 0.3 nmol L −1 for hydrogen peroxide detection was achieved. The zero current potential technique holds great promise for the construction of novel electrochemical sensors and the application to various targets assay. More details are discussed in the article by Zheng et al. on page 1174–1178. Abstract : The back cover picture shows a zero current potential technique for electrochemical sensing of hydrogen peroxide based on silver‐nickel nitrate hydroxide (AgNPs‐NNH). By using the AgNPs‐NNH nanocomposites, a very low detection limit of 0.3 nmol L −1 for hydrogen peroxide detection was achieved. The zero current potential technique holds great promise for the construction of novel electrochemical sensors and the application to various targets assay. More details are discussed in the article by Zheng et al. on page 1174–1178.